2011
DOI: 10.1007/s00244-011-9698-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Zinc to Several Aquatic Species Native to the Rocky Mountains

Abstract: National water-quality criteria for the protection of aquatic life are based on toxicity tests, often using organisms that are easy to culture in the laboratory. Species native to the Rocky Mountains are poorly represented in data sets used to derive national water-quality criteria. To provide additional data on the toxicity of zinc, several laboratory acute-toxicity tests were conducted with a diverse assortment of fish, benthic invertebrates, and an amphibian native to the Rocky Mountains. Tests with fish we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…Most toxicity testing with aquatic insects has involved field collections of the taxa of interest [13,43,53,54]. A practical constraint of this approach is that larvae need to be late enough in their development to be large enough to be captured, sorted, and confidently identified without injury and robust enough to be transported and to survive 4 d to 6 d of starvation before and during acute toxicity tests.…”
Section: Experimental Stream Results Relative To Field Patternsmentioning
confidence: 99%
“…Most toxicity testing with aquatic insects has involved field collections of the taxa of interest [13,43,53,54]. A practical constraint of this approach is that larvae need to be late enough in their development to be large enough to be captured, sorted, and confidently identified without injury and robust enough to be transported and to survive 4 d to 6 d of starvation before and during acute toxicity tests.…”
Section: Experimental Stream Results Relative To Field Patternsmentioning
confidence: 99%
“…5 Additionally, laboratory toxicity tests conducted with aquatic insects, particularly those using later instars, show much greater tolerance to metals compared to patterns observed in the field. 36,37 For contaminants that do not show significant acute toxicity (e.g., total dissolved solids, suspended sediments, nutrients, and deposition of metal oxides), traditional laboratory-based toxicity tests may be inappropriate and therefore should be supported by alternative approaches. 38 For example, using a field-based assessment, Linton 11 concluded that a more stringent benchmark for Fe would be necessary to protect mayflies and other grazers from the indirect effects of metal-oxide deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Although aquatic insects, particularly mayflies (Ephemeroptera), frequently are among the first taxa to disappear from metal‐contaminated freshwater ecosystems, laboratory testing typically indicates low sensitivity (Brix et al 2011; Poteat and Buchwalter 2014). For example, Brinkman and Johnston (2012) conducted acute zinc (Zn) toxicity tests with a variety of fish and insects native to western North America, and average median lethal concentrations (LC50s) for mayflies were approximately 80‐fold higher than those in fish. Although the US Environmental Protection Agency (1995) water quality criteria (WQC) for nickel (Ni) include a species mean acute value (SMAV) for the mayfly Ephemerella subvaria (Warnick and Bell 1969) among the 4 most sensitive species, a more updated Ni criteria for Illinois (Illinois Environmental Protection Agency 2002) included more sensitive crustaceans and mollusks, revealing that the Ephemerella SMAV was relatively insensitive (i.e., approximately an order of magnitude higher than those for the newly added 4 most sensitive species).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic insects are relatively poorly represented in WQC because most are difficult to culture. Frequently, aquatic insects used in testing are collected from streams as later instars (e.g., Warnick and Bell 1969; Brinkman and Johnston 2012). Poteat and Buchwalter (2014) advocated for the development of relevant insect toxicity models to bridge the gap in effect levels observed between field and laboratory data.…”
Section: Introductionmentioning
confidence: 99%